2003
DOI: 10.1210/jc.2003-030228
|View full text |Cite
|
Sign up to set email alerts
|

Placental Iodothyronine Deiodinase Expression in Normal and Growth-Restricted Human Pregnancies

Abstract: We have described the expression of specific iodothyronine deiodinase mRNAs (using quantitative RT-PCR) and activities in normal human placentas throughout gestation and compared our findings to those in placentas from pregnancies affected by intrauterine growth restriction (IUGR). The predominant deiodinase expressed in placenta was type III (D3); type II (D2) was also present. In general terms, the activities of the enzymes D2 and D3 (and mRNAs encoding these enzymes) were higher earlier in gestation (<28 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
85
2
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(96 citation statements)
references
References 47 publications
6
85
2
2
Order By: Relevance
“…Therefore, as an enzymatic barrier, placental D3 limits the exposure of the fetus to maternal thyroid hormones. In the human placenta, the enzyme activity, and mRNA and protein expression, of D2 are greatest in the first trimester compared with term, but significantly lower than those of D3 at all gestational ages studied (Koopdonk-Kool et al 1996, Chan et al 2003. These findings suggest that local production of T 3 may be important for early placental development, but is unlikely to contribute significantly to circulating T 3 concentrations in the fetus.…”
Section: Metabolism Of Thyroid Hormones In Uteromentioning
confidence: 78%
“…Therefore, as an enzymatic barrier, placental D3 limits the exposure of the fetus to maternal thyroid hormones. In the human placenta, the enzyme activity, and mRNA and protein expression, of D2 are greatest in the first trimester compared with term, but significantly lower than those of D3 at all gestational ages studied (Koopdonk-Kool et al 1996, Chan et al 2003. These findings suggest that local production of T 3 may be important for early placental development, but is unlikely to contribute significantly to circulating T 3 concentrations in the fetus.…”
Section: Metabolism Of Thyroid Hormones In Uteromentioning
confidence: 78%
“…In contrast, D3 has been localised to the villous ST cells and syncytial sprouts with expression in villous CTs focal and weak. In the third trimester villous ST expressed D2 and D3, whilst villous CTs were stronger for D2 than D3 (Chan et al 2003). The localisation of the deiodinases suggests that they may regulate the amount of maternal TH reaching fetal circulation.…”
Section: Iodothyronine Deiodinasesmentioning
confidence: 97%
“…Of the three deiodinating enzymes, only D2 and D3 have been identified in the placenta (Koopdonk-Kool et al 1996). Placental D3 activity is much greater (~200 times in first trimester and ~400 times at term) than D2 activity, however the activity and expression of both D2 and D3 falls as gestation progresses (Chan, et al 2003;Koopdonk-Kool et al 1996;Stulp, et al 1998). D2 is an outer ring deiodinase (Nelson, et al) found primarily in brain, pituitary, brown adipose tissue, thyroid and placenta with a preference for T 4 > rT 3 as a substrate (Figure 1).…”
Section: Iodothyronine Deiodinasesmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of deiodinases on the maternal side of the placenta may have consequences also on maternal TH levels as we know from consumptive forms of hypothyroidism that high expression of D3 in tumour tissue may lead to a substantial decrease in TH concentrations even in adulthood (63). According to immunohistochemical studies in human placenta, there is lower D3 expression in cytotrophoblasts compared with syncytiotrophoblasts, whereas D2 expression is more prominent in cytotrophoblasts (64,65).…”
Section: Utero-placental Unit and Th Homeostasismentioning
confidence: 99%